P106 Urgent need for bariatric surgery in Ireland. (13th September 2016) - O'Neill, K; Fitzgerald, A; Kearney, PM
Abstract : Background: With the prevalence of severe obesity and type 2 diabetes (T2DM) continuing to rise, bariatric surgery offers a successful treatment option. It is both clinically and cost effective, with the largest benefit among those with T2DM. Despite this, bariatric surgery is severely under-resourced in Ireland. Our aim is to estimate the number of people in Ireland who would potentially benefit from bariatric surgery based on established clinical criteria. Methods: Cross-sectional analysis of population based sample of adults aged ≥50 years who participated in wave 1 of TILDA (2009–2011) and attended the health assessment. Eligibility for bariatric surgery is based on two sets of criteria used to identify those most likely to benefit from surgery: firstly BMI > 35 kg/m² and ≥1 of T2DM, hypertension, sleep apnoea and previous MI. Secondly BMI > 35 kg/m², T2DM and ≥1 of elevated urine albumin creatinine ratio, retinopathy, neuropathy, previous MI and peripheral vascular disease. Analysis was carried out in Stata using the survey function (svy). TILDA prevalence estimates were applied to the 2011 census population to estimate absolute numbers meeting the criteria in Ireland. The diabetes remission rate (after 3-years follow-up) of 65% reported in the literature was applied to model the number of people with T2DM and complications (criterion 2) with potential remission of diabetes following surgery. Results: Among 5, 873 participants in TILDA, 584 had a BMI > 35 kg/m² (10.4% [95% CI: 9.57–11.28]). There were 112 participants with a BMI > 35 kg/m² and T2DM (2.06% [95% CI: 1.70–2.49]). In TILDA, 410 participants met the first set of criteria (7.38% [95% CI: 6.67–8.16]). Applying this prevalence estimate to the number of people aged ≥50 years in Ireland, in 2011, provides an estimate of 85, 244 (95% CI: 77, 113–94, 233) people potentially eligible for bariatric surgery. In TILDA, 50 participants met the second set of criteria (prevalence 0.97% [95% CI: 0.73–1.28]). Applying this prevalence estimate to the number of people aged ≥50 years in Ireland, in 2011, provides an estimate of 10, 891 (95% CI: 8, 228–14, 416) people aged ≥50 years eligible for bariatric surgery. Provision of bariatric surgery to this cohort of patients could potentially result in an estimated 7, 079 patients having acceptable glycaemic control not requiring medication. Conclusion: These data demonstrate the urgent need to provide clinical and cost-effective interventions for people with T2DM. In Ireland the provision of bariatric surgery to those in greatest need has the potential to improve both patient outcomes and reduce healthcare expenditure.